The Historical Roots of Social Assistance: An Inadequate Response to the Colonial Destruction of Mi’kmaw Livelihood in Nova Scotia - Cullen, Declan; Castleden, Heather; Wien, Fred (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Social assistance and related programs are an important part of life in the 13 Mi’kmaq communities of Nova Scotia. Given the substantive importance of social assistance and related programs in Mi’kmaq communities, it is surprising how little research has been conducted on the subject. This research aims to understand the origins of economic dependence and the related emergence of social assistance among the Mi’kmaq in Nova Scotia. We identify key historical periods and processes that have shaped the current policy landscape. A defining characteristic of social policy on reserve has been the fact that First Nations themselves have had very little say in how programs such as social assistance are designed and delivered. There is hope that a more self-determined and holistic approach may emerge.